Dead aim [large type] - Richards, Dusty (Richards, Dusty. O'Malley's of Texas, 2018)
"The oldest and boldest O'Malley brother, Long John takes on the challenge of riding shotgun on a wagon train across the hostile Nebraska Territory. But the real test lies in the journey ahead--to the Rocky Mountains, Sante Fe, and home to Texas--with perils that will either make him a living legend . . . or a dead one"--